Pemikiran Politik Ibnu Kholdun (732 H-808 H/1332-1406 M) - Solikah Solikah; Ismail Ismail (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, This study will examine how Ibnu Kholdun's political thought (732 H-808 H), in context as one of the Islamic thinkers who have contributed to the political system that once existed in the treasures of Islamic civilization. This research includes literature review, which focuses on the object of study in a particular literature, namely the work of Ibn Kholdun. The conclusions of this study are among others; that ‘ashabiyah is a certain socio-political characteristic contained in a tribe (community), and is in the village's cultural framework. Abi Ashabiyah is the driving force of a state and is the foundation of a state or dynasty. Ashabiyah has a major role in the expansion of the country after it was the foundation of the country's upholding. If ‘ashabiyah is strong, then the emerging country will be broad, on the contrary if‘ ashabiyah is weak, then the area of the emerging country is relatively limited. Ashabiyah can be a tool of struggle, an instrument of attack and defense. It can also be a tool for resolving conflicts between groups, that is, if this conflict must be resolved violently. In a settled society the ultimate goal of the Ashabiyah is Mulk, authority that ultimately weakens the will to be complied with, if necessary by force. When the state or dynasty or mulk is established, he will try to destroy ‘ashabiyah. Ibn Khaldun's thoughts about the state ‘ashabiyah had a very significant influence on the achievement of power and political continuity. Starting from the beginning of the movement to build strength, then continue to achieve victory, even to the stage of maintaining the social stability of the country. Conversely, the waning of ‘ashabiyah ties will potentially weaken the country's resilience from the onslaught of the enemy as well as from internal turmoil, and the changing times that are growing also play a role in testing and providing very heavy resistance as well. The country formed is based on ‘ashabiyah, usually three generations old, which is around 120 years. One generation is calculated for a person's normal age of 40 years.Keywords, Ashabiyah, Ibn Kholdun, Politics, and Siyasah